Foreign object detection for wireless power transfer system using YOLO-Fastest - Xie, Penghui (Nanyang Technological University, 2022)
With the rapid development of wireless power transmission technology, safety requirements during use are getting higher and higher. Due to the coupling air gap in its structure, foreign objects will inevitably be involved during work. The intervention of metal and biological foreign objects causes the system to deviate from the standard operating point and even cause safety accidents. Therefore, foreign object detection (FOD) technology has received widespread attention.